Carbon ion radiotherapy for basal cell adenocarcinoma of the head and neck: preliminary report of six cases and review of the literature - Jingu, Keiichi (BioMed Central, 2010)
BACKGROUND: Basal cell adenocarcinoma accounts for approximately 1.6% of all salivary gland neoplasms. In this report, we describe our experiences of treatment for BCAC with carbon ion radiotherapy in our institution. METHODS: Case records of 6 patients with diagnosis of basal cell adenocarcinoma of the head and neck, who were treated by carbon ion radiotherapy with 64.0 GyE/16 fractions in our institution, were retrospectively reviewed. RESULTS: In a mean follow-up period of 32.1 months (14.0-51.3 months), overall survival and local control rates of 100% were achieved. Only one grade 4 (CTCAE v3.0) late complication occurred. There was no other grade 3 or higher toxicity. CONCLUSIONS: Carbon ion radiotherapy should be considered as an appropriate curative approach for treatment of basal cell adenocarcinoma in certain cases, particularly in cases of unresectable disease and postoperative gross residual or recurrent disease.